Arti Strategis Membangun Merek yang Kuat (Tinjauan Literatur) - Muhammad Fikri Andhika; Nafiah Ariyani (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2025)
A brand can enhance a company's ranking, on the one hand, and consumers' status in society, on the other. The purpose of this paper is to further elaborate on the strategic significance of strong brand building efforts. The research design used in this study is a literature review. The data sources used are journals and/or websites related to the selected topic. The data sources for this study consist of journal articles on the strategic significance of brands. The data analysis technique used is content analysis. Companies in developing countries like Indonesia are increasingly recognizing the benefits of building strong brands, such as surviving difficult economic conditions, enjoying longer lifespans, gaining greater power in distribution channels, expanding sales beyond small domestic markets, becoming more competitive in staff recruitment and retention, and increasing profits. Brand strength plays a crucial role in determining business success, as it significantly shapes customer behavior, engagement, and loyalty. This is because a strong brand has strategic significance as a valuable asset for companies in making business decisions. By understanding and leveraging brand strength, companies can develop strategies that maximize their brand's potential and drive business growth. Furthermore, strong brand building plays a role in creating sustainable differentiation amidst increasingly fierce market competition. In today's digital age, consumers buy products not only based on their function but also on the values, image, and story behind the brand. Therefore, an effective brand strategy focuses not only on visuals or communication but also reflects the company's core values ​​that are relevant to consumer expectations and aspirations.